Testing the Multi-Theory Model for initiation and sustenance of smoking cessation at Kathmandu Metropolitan City, Nepal: A cross-sectional study - Sumitra SHARMA; Umesh R. ARYAL; Manoj SHARMA (Journal of Health and Social Sciences)
Introduction: Smoking and use of other tobacco products are a global public health threat. The objective of the study was to predict the initiation and sustenance of smoking cessation (SC) by applying the multi-the- ory model (MTM) of health behavior change. Methods: In a cross-sectional study, the face-to-face interview was conducted by visiting different public places and coffee shops in Kathmandu Metropolitan, Nepal. A 30-item valid and reliable MTM-based survey instrument was administered to the participants who smoked cigarettes. Stepwise multiple regres- sions were conducted to explain SC behavior. The entire value of the Cronbach alpha coefficient (α) of the subscales and the scale was 0.91 which is excellent internal consistency. Results: A total of 132 participants completed the study (93.6%). The median age of participants was 35.53 years and 75% of them were males. The median number of cigarettes smoked per day was 7. Behavioral con- fidence (β = 0.06, P = 0.02) and changes in the physical environment (β = 0.11, P = 0.01) were significant predictors for the initiation of SC. Next, emotional transformation (β = 0.25, P < 0.001) was a significant predictor for sustenance for SC. Conclusion: MTM has the usefulness to assess both the initiation and sustenance behavior of SC. Poten- tial solutions using MTM constructs should be developed in future interventions to change behavior of SC.